Prehospital Cardiac Arrest Management: A Narrative Review (The Review of Diabetic Studies, 2025)
Out-of-hospital cardiac arrest (OHCA) is a global health issue with high mortality and morbidity. Prehospital management is crucial for improving survival and neurological outcomes. This narrative review examines the epidemiology, global burden, survival rates, and the importance of early prehospital interventions in OHCA. The incidence of EMS-treated OHCA ranges from 30 to 97 per 100,000 population annually, with survival to hospital discharge rates between 8.6% and 9.9%. Age is a significant factor, with the median age of OHCA cases between 65 and 70 years. Survival rates vary widely by region, partly due to differences in EMS systems, bystander CPR rates, and AED availability. Early, effective prehospital interventions, such as high-quality CPR, rapid defibrillation, and appropriate airway management, significantly influence outcomes. The chain of survival concept guides prehospital care, emphasizing early recognition, high-quality CPR, rapid defibrillation, advanced care, and post-resuscitation management. Challenges in prehospital settings include limited resources, environmental factors, and decision-making complexity. Emerging technologies, such as mechanical CPR devices, extracorporeal CPR, and point-of-care ultrasound, show promise in enhancing care. International guidelines from the American Heart Association, European Resuscitation Council, and Asian perspectives provide evidence-based recommendations for prehospital management. However, regional variability in EMS systems and barriers in low-resource settings highlight the need for context-specific strategies. Future directions include optimizing paramedic education, refining termination of resuscitation protocols, and integrating innovative technologies to improve OHCA outcomes globally.